Clinical Biochemical Diagnosis of Acute Kidney Injury Using Neutrophil Gelatinase-Associated Lipocalin (NGAL): A Narrative Review - Naji, Zainab Abdul Wahed (American Journal of Bioscience and Clinical Integrity, 2026)
Acute kidney injury (AKI) is a severe clinical disorder when the renal function starts to deteriorate rapidly, resulting in the accumulating of metabolic wastes and electrolyte and fluid imbalance. The early diagnosis of AKI has continued to pose a significant issue in clinical practice due to the fact that the traditional biomarkers, including serum creatinine and the blood urea nitrogen, tend to increase when the kidney is already damaged to a great extent. Over the recent years, neutrophil gelatinase associated lipocalin (NGAL) has been developed as a promising early biomarker to detect and monitor AKI. This narrative review will summarize the existing evidence on the clinical biochemical usefulness of NGAL in diagnosing and prognosing acute kidney injury. NGAL is a minor glycoprotein that is released by damaged tubular epithelial cells of the kidney and activated neutrophils in reaction to renal stress, ischemia or toxin damage. Because of its quick excretion into the plasma and urine within several hours of renal insult, it is a very sensitive marker of kidney damage early onset. It has been demonstrated by a considerable amount of experimental and clinical evidence that NGAL levels increase much sooner than classical renal biomarkers and allow an earlier diagnosis, risk selection, and timely therapeutic intervention. Furthermore, NGAL has presented potential usefulness in a number of clinical practices such as sepsis-related AKI, allopatric surgery-related renal injury, contrast-related nephropathy, and critical illness. These immunoassays or biosensor-based technologies of measuring NGAL have further increased its utility in clinical laboratories of routine. In view of these encouraging results, there are still certain limitations such as cutoff variability, effects of systemic inflammation as well as absence of universal standardization of tests. Altogether, NGAL is a potent biochemical indicator that would greatly enhance the early clinical diagnosis and treatment of AKI in combination with other traditional renal functional tests and clinical examination.